2001
DOI: 10.1016/s0306-5456(01)00270-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour with a viable infant: a randomised clinical trial comparing intravaginal misoprostol and intravaginal dinoprostone

Abstract: Objective To compare the efficacy and safety of vaginal misoprostol (50mg) with vaginal dinoprostone.Design Double-blind randomised trial.Participants 370 patients with medical indications for induction of labour.Outcome measures Vaginal deliveries within 24 hours, as well as time to vaginal deliveries, caesarean rates, costs, and fetal, neonatal and maternal condition. Results Compared with vaginal dinoprostone, vaginal misoprostol resulted in greater efficacy in several areas:vaginal delivery within 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
7
2
7
Order By: Relevance
“…No significant differences between the groups with respect to maternal and neonatal outcomes was noted. Thus, in agreement with other studies, 3,7,8,10,11,24,27,29,30 all measures of fetal tolerance of the treatment, umbilical cord pH, the Apgar score and frequency of admission to the neonatal intensive care unit, were the same. The incidence of uterine hyperstimulation, which is commonly thought to be elevated by administration of misoprostol, was low and similar in all three groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant differences between the groups with respect to maternal and neonatal outcomes was noted. Thus, in agreement with other studies, 3,7,8,10,11,24,27,29,30 all measures of fetal tolerance of the treatment, umbilical cord pH, the Apgar score and frequency of admission to the neonatal intensive care unit, were the same. The incidence of uterine hyperstimulation, which is commonly thought to be elevated by administration of misoprostol, was low and similar in all three groups.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in disagreement with most, 3,6,8 but not all, 4 studies that have demonstrated a higher incidence of hyperstimulation associated with fetal distress in women treated with misoprostol group. In our study, 100 microgram tablets of misoprostol were cut into four pieces of equal size, which might not always have been placed in the posterior fornix, due to difficulties in handling such small pieces, which could explain the unexpected reductions in efficacy and hyperstimulation.…”
Section: Discussioncontrasting
confidence: 80%
“…[7][8][9] In the present study, the main indication was PROM (38.6%) followed by PDP (28.6%). The reason may be that after reaching term, the efficiency of placenta starts to diminish and the foetus suffers increasingly from anoxia.…”
Section: Discussionmentioning
confidence: 77%
“…12 Other minor side effects in the mother were nausea; vomiting; diarrhea; rashes; dizziness; abdominal pains and flatulence.1,1 1 Passage of meconium, low Apgar scores and increased Caesarean section for foetal heart rate abnormalities have been observed in the foetus. 7 The optimal route and safe dosage o f misoprostol is still being studied. Misoprostol tablets can be given intra-vaginally, sublingually, rectally and orally as a suspension.2,13 Most studies in the literature have used the intravaginal route.3,5,6 The side effects of vaginal misoprostol are dose related.12 The current drug formulation of two hundred microgram 200pg tablet available in our country is difficult to break into a measurable dose.…”
Section: Introductionmentioning
confidence: 99%